Sustainable food packaging: An updated definition following a holistic approach - Dörnyei, Krisztina Rita; Uysal-Unalan, Ilke; Krauter, Victoria; Weinrich, Ramona; Incarnato, Loredana; Karlovits, Igor; Colelli, Giancarlo; Chrysochou, Polymeros; Fenech, Margaret Camilleri; Pettersen, Marit Kvalvåg; Arranz, Elena; Marcos, Begonya; et al. (Frontiers in Sustainable Food Systems, 2023)
Food packaging solutions need to be redesigned to be more sustainable, but determining which solution is ‘better’ is a very difficult task when considering the entire food product value chain. Previous papers paved the way toward a sustainable food packaging definition, but it is far from being commonly accepted or well usable in the broad food systems domain, which further results in uninformed choices for sustainable food packaging made by all stakeholders in the value chain: producers, distributors, practitioners and consumers. Therefore this work aims first at giving a state-of-the-art overview of sustainable food packaging terms (37 similar terms were identified and grouped into four clusters: Sustainable, Circular, Bio and Other sustainable packaging) and definitions using systematic (narrative) review analysis. Second, it aims to offer an updated definition for sustainable food packaging, which is also specific to food packaging and be simple, coherent, easily understandable, and communicable to everybody. The applied holistic approach intends to include all aspects of the food-packaging unit, to consider food safety and packaging functionality, while taking into account different disciplines and challenges related to food packaging along the supply chain. Being a balancing act, a sustainable food packaging may not be a perfect solution, but contextual, suboptimal and in need of constant validation.